Tools of Transport Telematics 15th International Conference on Transport Systems Telematics, TST 2015, Wrocław, Poland, April 15-17, 2015. Selected Papers - Mikulski, Jerzy (Communications in Computer and Information Science, 2015)
This book constitutes the proceedings of the 15th International Conference on Transport Systems Telematics, TST 2015, held in Wrocław, Poland, in April 2015. The 35 revised full papers and two short papers included in this volume were carefully reviewed and selected from 115 submissions. The papers provide an overview of solutions being developed in the fields of transport telematics and intelligent transport systems.